2019
DOI: 10.1787/726fd39d-en
|View full text |Cite
|
Sign up to set email alerts
|

Hello, World

Abstract: Artificial Intelligence (AI) is an area of research and technology application that can have a significant impact on public policies and services in many ways. In just a few years, it is expected that the potential will exist to free up nearly one-third of public servants' time, allowing them to shift from mundane tasks to high-value work. Governments can also use AI to design better policies and make better decisions, improve communication and engagement with citizens and residents, and improve the speed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 28 publications
0
8
0
2
Order By: Relevance
“…Comme l'ont montré Berryhill et al (2019), ces dernières années ont été marquées par un intérêt renouvelé pour l'IA et ses éventuelles applications au sein de l'administration publique. La montée en puissance du secteur, les progrès technologiques et la démocratisation des ordinateurs et de la programmation comptent parmi les facteurs identifiés de cette résurgence (Berryhill et al, 2019).…”
Section: Processus De Décision Automatisé Et Recours à L'intelligenceunclassified
See 1 more Smart Citation
“…Comme l'ont montré Berryhill et al (2019), ces dernières années ont été marquées par un intérêt renouvelé pour l'IA et ses éventuelles applications au sein de l'administration publique. La montée en puissance du secteur, les progrès technologiques et la démocratisation des ordinateurs et de la programmation comptent parmi les facteurs identifiés de cette résurgence (Berryhill et al, 2019).…”
Section: Processus De Décision Automatisé Et Recours à L'intelligenceunclassified
“…Comme l'ont montré Berryhill et al (2019), ces dernières années ont été marquées par un intérêt renouvelé pour l'IA et ses éventuelles applications au sein de l'administration publique. La montée en puissance du secteur, les progrès technologiques et la démocratisation des ordinateurs et de la programmation comptent parmi les facteurs identifiés de cette résurgence (Berryhill et al, 2019). Certains ont suggéré que le codage des règles pourrait favoriser le recours aux processus de décision automatisés et à l'IA fondée sur des règles au sein de l'administration publique, ce qui présuppose l'existence de mécanismes de recours à l'arbitrage humain.…”
Section: Processus De Décision Automatisé Et Recours à L'intelligenceunclassified
“…As Berryhill et al (2019) have highlighted, the last several years have seen renewed interest in AI and its potential applications in government. The growing maturity of the field, improvement in technology and the democratisation of computers and programming are among the factors that have been nominated as factors driving this resurgence (Berryhill et al, 2019). It has been suggested that RaC could aid the use of automated decision making and rules-based AI in government, presupposing that avenues for appeal to human arbitrators exist.…”
Section: Automated Decision Making and Ai-enablementmentioning
confidence: 99%
“…For AI, several areas of use cases have been found, where the merits are uncontested. 17 For blockchain, the jury is still out.…”
Section: Box 23 Determining An Ambition Level and Risk Appetitementioning
confidence: 99%
“…1. There was an early efforts stage for public sector blockchain, which, in this report, is limited to the OECD publication Blockchains Unchained (Berryhill, Bourgery and Hanson, 2018 [17]).…”
Section: From Early Efforts Toward Maturitymentioning
confidence: 99%